Glycogen synthase kinase 3β (GSK3β) and presenilin (PS) are key regulators of kinesin-1-mediated cargo motility within axons - Banerjee, Rupkatha; Gunawardena, Shermali (Frontiers in Cell and Developmental Biology, 2023)
It has been a quarter century since the discovery that molecular motors are phosphorylated, but fundamental questions still remain as to how specific kinases contribute to particular motor functions, particularly in vivo, and to what extent these processes have been evolutionarily conserved. Such questions remain largely unanswered because there is no cohesive strategy to unravel the likely complex spatial and temporal mechanisms that control motility in vivo. Since diverse cargoes are transported simultaneously within cells and along narrow long neurons to maintain intracellular processes and cell viability, and disruptions in these processes can lead to cancer and neurodegeneration, there is a critical need to better understand how kinases regulate molecular motors. Here, we review our current understanding of how phosphorylation can control kinesin-1 motility and provide evidence for a novel regulatory mechanism that is governed by a specific kinase glycogen synthase kinase 3β (GSK3β) and a scaffolding protein presenilin (PS).